Architectural drafting and design - Jefferis, Alan; Madsen, David A.; Madsen, David P. (Delmar Cengage Learning, 2011)
ARCHITECTURAL DRAFTING AND DESIGN, 6E is ideal for all architectural drafters and CAD operators, whether beginning, intermediate, or advanced. The basics of residential design, commercial drafting, basic materials used for construction, common construction methods, and drawings typically associated with commercial construction are all covered in this comprehensive book, which is written to meet the most recent editions of IRC and IBC. Readers will be introduced to the various types of projects that a designer or architect is likely to complete during the actual design process and will gain the knowledge necessary to complete the drawings required by most municipalities to obtain a building permit for a single-family residence